Hydrothermal Carbonization of Biomass Residues: Mass Spectrometric Characterization for Ecological Effects in the Soil–Plant System. Issue 1 (1st January 2013) - Jandl, Gerald; Eckhardt, Kai‐Uwe; Bargmann, Inge; Kücke, Martin; Greef, Jörg‐Michael; Knicker, Heike; Leinweber, Peter
Abstract : Hydrochars, technically manufactured by hydrothermal carbonization (HTC) of biomass residues, are recently tested in high numbers for their suitability as feedstock for bioenergy production, the bioproduct industry, and as long‐term carbon storage in soil, but ecological effects in the soil–plant system are not sufficiently known. Therefore, we investigated the influence of different biomass residues and process duration on the molecular composition of hydrochars, and how hydrochar addition to soils affected the germination of spring barley ( Hordeum vulgare L.) seeds. Samples from biomass residues and the corresponding hydrochars were analyzed by pyrolysis‐field ionization mass spectrometry (Py‐FIMS) and gaseous emissions from the germination experiments with different soil–hydrochar mixtures by gas chromatography/mass spectrometry (GC/MS). The molecular‐level characterization of various hydrochars by Py‐FIMS clearly showed that the kind of biomass residue influenced the chemical composition of the corresponding hydrochars more strongly than the process duration. In addition to various detected possible toxic substances, two independent mass spectrometric methods (Py‐FIMS and GC/MS) indicated long C‐chain aliphatic compounds which are typically degraded to the C2 –unit ethylene that can evoke phytotoxic effects in high concentrations. This showed for the first time possible chemical compounds to explain toxic effects of hydrochars on plant growth. It is concluded that the HTC process did not result in a consistent product with defined chemical composition. Furthermore, possible toxic effects urgently need to be investigated for each individual hydrochar to assess effects on the soil organic matter composition and the soil biota before hydrochar applications as an amendment on agricultural soils.